2019
DOI: 10.1002/term.2958
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of human bone marrow‐derived mesenchymal stromal/stem cells on peripheral blood T cells from rheumatoid arthritis patients

Abstract: Rheumatoid arthritis (RA) is a Th1/Th17‐mediated autoimmune disease whose current treatment, consisting in the blockage of inflammatory cytokines by disease‐modifying antirheumatic drugs, is not effective for all patients. The therapeutic potential of mesenchymal stromal/stem cells' (MSCs) immunomodulatory properties is being explored in RA. Here, we investigate the effect of human bone marrow (BM)‐MSCs on the expression of cytokines involved in RA physiopathology by the distinct functional compartments of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have extensive immunomodulatory effects, such as inhibiting T cell proliferation, activation and cytokine production; however, the detailed mechanism by which MSCs regulate T cells remains poorly defined [15,16]. In the present study, we found that the percentage of CD4+CD25+Foxp3+ cells in the CD4+ T cell population was significantly decreased, while the percentage of CD4+CD3+RORrt+ cells was significantly increased after a coculture with MSCs.…”
Section: Discussionmentioning
confidence: 46%
“…Mesenchymal stem cells (MSCs) have extensive immunomodulatory effects, such as inhibiting T cell proliferation, activation and cytokine production; however, the detailed mechanism by which MSCs regulate T cells remains poorly defined [15,16]. In the present study, we found that the percentage of CD4+CD25+Foxp3+ cells in the CD4+ T cell population was significantly decreased, while the percentage of CD4+CD3+RORrt+ cells was significantly increased after a coculture with MSCs.…”
Section: Discussionmentioning
confidence: 46%
“…Inflammatory cytokines including tumor necrosis factor- (TNF-) α , interleukin- (IL-) 1 β , IL-6, and IL-17 play a critical role in the pathogenesis of RA. Specifically, TNF- α , IL-1 β , and IL-17 induce RA synovitis with the promotion of vasospasm and cause bone destruction in late-stage synovitis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rashedi et al[ 47 ] have reported that MSCs can either increase the level of Treg cells by directly interacting with Tregs through the Notch signaling pathway or indirectly induce CD4 + lymphocytes to differentiate into Treg cells[ 47 ]. In addition, bone marrow-derived MSCs can also inhibit the production of inflammatory cytokines by T cells in RA[ 48 ]. The significant anti-inflammatory role of MSCs on T cells is mainly dependent on hindering the nuclear factor-κB signaling pathway[ 49 ], which has been well recognized as the pivotal downstream signaling pathway involved in rheumatic disease pathogenesis[ 50 ].…”
Section: Discussionmentioning
confidence: 99%